ANALISIS PENGARUH HARGA, KEBUTUHAN MENCARI VARIASI, DAN WORD OF MOUTH DALAM PERILAKU BRAND SWITCHING PADA MINUMAN BERSODA COCA-COLA KE BIG COLA - Firdaus, Muhammad Irfan; Rahardjo, Mudji (Diponegoro Journal of Management, 2015)
Brand switching is one of the most appealing objects to be studied. Companies need to know what motivate consumer to switch and using competitor’s product. This paper will specifically use carbonated beverage market in Indonesia as the object of study. The purpose of this study is to test the strength of the price, the variety-seeking and the word of mouth in regards to brand switching on carbonated beverage productnamely Coca-Cola and Big Cola brand. Independent variables used in this research consisted of price (X1), the need for variation (X2) and word of mouth (X3), while the dependent variable is brand switching (Y).The sample consisted of 100 respondents in Semarang City, which was taken using purposive sampling technique. The analysing tool is SPSS 21.0 which used to complete validity test, reliability test, the classic assumption test, multiple linear regression analysis, hypothesis testing via F test and t test, and analysis of the coefficient of determination (R²). Based from the analysis, the regression equation is: Y = 0,314X1 + 0,226 X2 + 0,228 X3Price showed achieved the highest regression coefficient and it can be concluded that this variable is the most influencing factor in brand switching for carbonated beverage product. The second most important factor is the word of mouth, which later followed by need for variation. The coefficient of determination (adjusted R2) is 0.557, or 55.7 percent. This means the model is good enough. All three independent variables in this study can explain 55.7 percent of the variable Brand Switching. While the remaining 44.3 percent is explained by other variables outside of the three variables used in this study.